Designing an Intellectual Capital Evaluation Model in Knowledge-Based Companies - MirAli Seyyed Naghavi; Mohamad Khosravi; Hamed Dehghanan; Vahid Nasehifar (مطالعات مدیریت بهبود و تحول, 2022)
This research is a mixed-exploratory and goal-oriented, applied-developmental study and its purpose is to identify components, indicators, metrics to evaluate intellectual capital in knowledge-based companies. In the qualitative section, with the help of Semi-structured interviews, a deeper assessment of the perception and attitude of the target community was conducted. In addition, the necessary information about the research objectives was obtained by reviewing the research literature (field study) and through Delphi method and expert questionnaire by 12 professors, experts and managers of knowledge-based companies, the conceptual model was approved and the questionnaire was finalized for testing. . In the quantitative part of the research, the data obtained from the qualitative part were compiled in the form of a questionnaire and completed by 153 managers of knowledge-based companies located in Tehran Science and Technology Park. Finally, four components of human capital - structural capital - communication capital - innovation capital and 17 The index and 78 related metrics were identified and classified and the relationships between the components were evaluated and finalized using the structural equation model.